Effect of Early Childhood Education Training Programmes on Child Development - Nazir Haider Shah; Asghar Abbas; Anita Shuja (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The purpose of the study is to investigate the effect of early childhood education (ECE) training programmes on child development. The study is descriptive in nature and a survey method was applied for the collection of data. Ninety (90) teachers and heads of pre-schools of Taxila city were included in the population. A research questionnaire based on five-point Likert scale was used to collect the data and the questionnaire was personally administered by the researcher. Chi-Square association test was utilized to explore the association between responses of the students and percentage was also used for data analysis. The majority of teachers mentioned that ECE training programmes offer multiple skills for teachers such as use of instructional resources, knowledge competencies of teachers, comprehension of content, and principles of the learning process. Further ECE training programmes effectively contribute into the developmental process of child while providing diversity of professional development concepts. The study recommended that to make the teaching process more effective and to get better results in the field of education, teachers may have pedagogical skills to improve classroom management.